The Effect of Achyranthes aspera Extracts on Mild Steel Corrosion in Industrial Water Medium. (28th May 2013) - Kumar, Chikkur B. Pradeep; Mohana, Kikkeri N.
Abstract : Achyranthes aspera (AA) extracts were studied as corrosion inhibitor for mild steel (MS) in industrial water medium using mass loss and electrochemical techniques. The results of the study revealed that AA extracts inhibit MS corrosion through adsorption process following Langmuir adsorption isotherm model. The protection efficiency increased with increase in inhibitor concentration and decreased with temperature. The electrochemical impedance spectroscopy (EIS) measurements showed that the charge transfer resistance increases with increase in the concentration of AA extracts. The polarization curves obtained indicate that AA extracts act as mixed type of inhibitor. Scanning electron microscopy (SEM) was used to analyze the surface adsorbed film.